(untitled) (Economics and region, 2018)
The article deals with the concept of state regulation of the construction industry. It is analyzed and economically substantiated the main disadvantages of the process of state regulation of the construction industry. The ways of improvement of state building-architectural control are investigated and prospects of development of construction industry are determined